Design and experiment of automatic garlic seed directing device - Geng, Aijun; Li, Xiaoyu; Hou, Jialin; Zhang, Ji; Zhang, Zhilong; Chong, Jun (International Journal of Agricultural and Biological Engineering, 2020)
Garlic planting requires a single seed with a scaly bud upward and vertically. In this study, an automatic garlic seed directing device was designed for auxiliary garlic seeding by utilizing a seed placed funnel, a correcting mechanism, and an automatic control system. Three factors influenced device performance: characteristics of garlic seeds, limited notch diameter of the seed placed funnel, and funnel taper of the seed placed funnel. The most optimal structural parameters of the seed placed funnel were determined via theoretical analysis. The research samples of Lanling and Jinxiang garlic were divided into three groups according to their respective sizes. 3D design software (Solidworks) was used to simulate the above three factors and analyze their rules of action. The obtained simulation results demonstrated that the suitable range of funnel taper and limited notch diameter of seed placed funnel for the three groups of seed were from 40° to 60° and 6-8 mm, respectively. The bench test showed that when the funnel taper was 60° and the limited notch diameter was 10 mm, the success rates of the three groups’ seeds in terms of scaly bud directing were 89.8%, 91.6% and 96.6% respectively, which satisfied the agricultural requirements of garlic planting. Accordingly, the corresponding results may promote the study and improvement of garlic intelligent planting equipment.Keywords: garlic, garlic seed directing, simulation and analysis, automatic controlDOI: 10.25165/j.ijabe.20201306.5142Citation: Geng A J, Li X Y, Hou J L, Zhang J, Zhang Z L, Chong J. Design and experiment of automatic garlic seed directing device. Int J Agric & Biol Eng, 2020; 13(6): 85–93.